The Greek Ethnography. A critical overview - Aris Tsantiropoulos (EtnoAntropologia)
This article presents an overview of Greek ethnography. It argues that ethnography in Greece cannot be seen as separate from its preceding fields of history and folklore studies, alongside Greece itself being viewed as a research field by foreign anthropologists. Because of the late introduction of anthropology in Greece it followed very quickly the main theoretical stream of postmodernism in its view of Greek society. The main argument of this article is that the introduction of postmodernism in Greek Anthropology prevented a dialogue with the pre-existing field research work that had been conducted in Greece by non Greek Ethnographers and Greek Folklorists or Historians. This fact has specific consequences at the epistemological, theoretical and methodological level of contemporary Greek Ethnography.